Solitary and multifocal ground glass opacities—a narrative review of current management and future directions in the face of increasing incidence of detection - Khaliq, Urhum; Dezube, Aaron; Burrows, Whitney; Chai, Louis F. (Current Challenges in Thoracic Surgery, 2026)
Background and Objective: Ground-glass opacities (GGOs), or subsolid nodules, are hazy areas of increased density seen on high-resolution computed tomography (CT) that are not associated with underlying vessels or bronchial walls, as defined by the Fleischner society. Current management remains subjective. We review the current literature and developments regarding GGOs. Additionally, we review management of multifocal GGOs (mGGO) utilizing existing data on solitary GGOs. The objective of this study is to provide an overview of GGOs including diagnosis, surveillance, and management.Methods: We conducted a literature review for GGOs that looked at monitoring/surveillance, diagnosis, and treatments for GGOs indexed on PubMed that were written in English.Key Content and Findings: GGOs are subsolid nodules primarily diagnosed by CT. When appropriate, tissue sampling is indicated by open or minimally invasive methods. Guidelines currently vary for pure GGO (pGGO) versus part-solid GGO (psGGO). While minimally invasive ablation yields excellent overall survival (OS) of 96.4%, recurrence remains high and has been reported up to 30.3%. In high-risk patients, stereotactic body radiotherapy remains a viable option with 3-year OS of 100% for GGO and 59% for psGGO. In medically fit patients, surgical resection remains the gold standard for diagnostic and therapeutic purposes. Artificial intelligence and machine learning have shown early success, with the role of tumor biomarkers being investigated. mGGOs still represent a treatment challenge, and while duration and size may guide management, future innovation is needed to optimize lung preservation.Conclusions: The incidence of GGO diagnosis has rapidly increased in recent years, which has been creating challenges in clinical decision making. Given that GGOs can arise from many different causes only makes the evaluation more challenging. Although current guidelines exist, there remains provider and practice-based variability. The evaluation and treatment are particularly challenging in the setting of mGGOs. Advances in molecular testing, diagnostic imaging, tissue sampling, and treatment methods can help with standardization.